2023
DOI: 10.3390/agriculture13050992
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Multivariate Methods for the Selection of High-Yielding Rapeseed Lines with Varied Seed Coat Color

Abstract: A crucial aim for rapeseed breeders is increasing the seed yield through improving yield- and silique-related traits. In this research, traits including the number of seeds per silique, silique length, silique width, and thousand-seed weight combined with seed coat color were investigated. Yellow-seeded lines of oilseed rape have a thinner seed coat, lower fiber content, and higher protein and oil content than traditional varieties. Hybrids of yellow- and black-seeded Brassica napus, which combine the advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…When the sample size is sufficient and relatively balanced, theoretically, a more accurate identification of a greater range of colors can be achieved by selecting more calibrated colors. Hyperspectral analysis is a key technology and method for achieving high-throughput analysis of crops [1,58,[62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the sample size is sufficient and relatively balanced, theoretically, a more accurate identification of a greater range of colors can be achieved by selecting more calibrated colors. Hyperspectral analysis is a key technology and method for achieving high-throughput analysis of crops [1,58,[62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…In general, yellow rapeseed has a thinner seed coat, a lower percentage of hulls, and a larger embryo compared to other colors. Research indicates that rapeseeds with a more yellowish and lighter color tend to have higher oil content, as well as higher levels of oleic and linoleic acids, while also exhibiting higher protein content and lower fiber content [1,2]. Since the color of the rapeseed coat is controlled by its corresponding gene, it has become an important trait for breeding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Special Issue "Germplasm Resources Exploration and Genetic Breeding of Crops" was planned to cover all aspects of the characterization of crop genetic resources and their applications in breeding, as well as genetics research and molecular breeding, including gene/QTL detection or gene functional analysis in crops. In our Special Issue, we have united 16 papers addressing various aspects around the topic of plant genetic resources, including quantitative trait loci (QTL) mapping/gene discovery [2,3], genetic diversity/variation [4][5][6][7][8][9], breeding products [9][10][11][12][13], and genetic resource profiles for crops [14][15][16].…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…Finally, Łopaty ńska et al [14] assessed double haploid oilseed rape lines with varied seed coat color and selected valuable breeding material connecting a light color of seeds with high yielding. Based on the obtained results, the authors concluded that the most crucial factors in breeding rapeseed with improved seed properties are seed weight and color.…”
Section: Breeding Resources and Breeding Productsmentioning
confidence: 99%